Perancangan Baru Panti Asuhan Muhammadiyah Sumur Di Kota Bandung Dengan Pendekatan Psikologi - Fatikah Ichsan, Marsa; Hanum, Imtihan; Laksitarini, Niken (Telkom University, 2024)
Orphanages are social institutions responsible for providing social welfare services to children in need to achieve a better life. Orphanages function as substitute families, with caregivers acting as parents in meeting the developmental needs of children. Children living in orphanages have the right to education, a good environment, health facilities, and adequate nutrition. Data from the Indonesian Ministry of Social Affairs shows that the number of abandoned children has reached 67,368, and the number of orphans has reached 106,406, with 4,800 of them in orphanages, most of which are located on the island of Java. Research shows that 94% of children in orphanages are not orphans, but come from underprivileged families. Life in an orphanage can cause psychological problems for children, such as feelings of inferiority, apathy, and difficulties in social relationships. However, there are still many orphanages in the city of Bandung that experience limited facilities for child care. Therefore, planning needs to be done to meet the needs and feasibility of orphanages both in terms of facilities and paying attention to the psychological condition of children. Keywords: orphanage, children, psychic